An Integrative Review of Strength Milestoning in Mid-Stage Achilles Tendon Rehab - Toland, Chris; Cronin, John; Reid, Duncan; Laughlin, Mitzi; Fleeks, Jeremy (MDPI, 2025)
Current rehabilitation protocols for transitioning patients to late-stage recovery, evaluating return-to-play (RTP) clearance, and assessing tendon characteristics exhibit significant heterogeneity. Clinicians frequently interpret and apply research findings based on individual philosophies, resulting in varied RTP criteria and performance expectations. Despite medical clearance, patients recovering from Achilles tendon (AT) injuries often exhibit persistent impairments in muscle volume, tendon structure, and force-generating capacity. Inconsistencies in assessment frameworks, compounded by a lack of quantitative data and the utilization of specific metrics to quantify certain strength characteristics (endurance, maximal, explosive, etc.) and standardized protocols, hinder optimal functional recovery of the plantar flexors during the final stages of rehabilitation and RTP. With this in mind, the aim of this integrative review was to provide an overview of AT rehabilitation, with particular critique around mid-stage strengthening and the use of the heel-raise assessment in milestoning rehabilitation progress. From this critique, new perspectives in mid-stage strengthening are suggested and future research directions identified.